Do ESG factors improve utilities corporate efficiency and reduce the risk perceived by credit lending institutions? An empirical analysis. (April 2023) - Veltri, Stefania; Bruni, Maria Elena; Iazzolino, Gianpaolo; Morea, Donato; Baldissarro, Giovanni
Abstract: In a changed scenario, characterized by great attention to environmental, social, and governance (ESG) factors, few industries feel the pressure more than utilities. The paper investigates, by employing a Data Envelopment Analysis (DEA) model, whether including ESG factors increases the efficiency of utilities companies and whether banks, by considering ESG ratings when selecting utilities companies, succeed in optimizing their portfolio. Our findings signal that ESG factors neither improve utilities efficiency nor constitute a useful complementary criterion for credit lending managers, provide useful suggestions for managers, regulators and academics. Highlights: Environmental, social, and governance (ESG) factors are subject to increasing interest. Few industries feel the pressure more than utilities, a controversial sector highly exposed to reputational risks. The paper investigates whether including ESG factors increases the overall efficiency of utilities companies. The paper also investigates whether banks, selecting utilities companies by ESG ratings, mitigate their credit risk. Our findings provide evidence that ESG factors neither improve utilities' efficiency nor mitigate banks' credit risk.